Forms and degrees of repetition in texts : detection and analysis - Altmann, Gabriel; Köhler, Reinhard (Quantitative linguistics, 2015)
The volume presents objective methods to detect and analyse various forms of repetitions. Repetition of textual elements is more than a superficial phenomenon. It may even be considered as constitutive for units and relations in a text: on a primary level when no other way exists to establish a unit, and on a secondary, artistic level, where repetition is a consequence of the transfer of the equivalence principle.